RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN PADA CV GARASITRIFT MENGGUNAKAN FRAMEWOK CODEIGNITER - Fery Oktabrian (2023)
The payroll system is one of the vital things in the financial activities of a company. CV Garasitrift, which is a company in the clothing sector, still uses a manual payroll system and attendance joins the right bank of the coffee. To meet the needs of the payroll system, an update on payroll is needed. One of the benefits of a payroll applicat ion is preventing data corruption, data loss, and data duplication. In conducting research analysis the authors use the PIECES method in determining future system requirements. In addition, for further system development, the author uses the Waterfall Meth od to adjust the needs of the system being developed through the results of interviews with prospective users. Application development is used using Sublime Text Tools as a text editor, then Figma tools as User Interface design, and MySQL as data storage t o the database. The author hopes that by making this payroll information system it can save time, and can create a secure data storage facility for CV Garasitrift Staff in paying employee payroll.